The Female Gentleman and the Myth of Englishness in the Detective Novels of Dorothy L. Sayers and Margery Allingham - Zsámba, Renáta (Hungarian Journal of English and American Studies, 2020)
Golden Age detective fiction by women offers insights into the competing gender ideologies of the 1930s and early 1940s. The female protagonist these novels delineate is called “the female gentleman” by Melissa Schaub, who describes her as the detective’s equal based on her intellectual abilities and independence. Although the female gentleman seems a revolutionary figure as she is forward-looking in gender politics, her strong belief in class hierarchy, her Victorian morals and relationship with the gentleman detective relocate her in the heritage of the English pastoral. This essay focuses on the female gentleman as a bridge figure whose marriage to the detective not only restores him to his masculinity but also portrays the woman embedded in the pastoral idyll of the English landscape. Her decision to accept traditional femininity reinforces the female gentleman’s role in the recreation of the stability and security of pre-war England. (RZs)